The importance of being mature: the effect of demographic maturation on global per-capita GDP - Rafael Gómez; Pablo Hernández de Cos (European Central Bank (ECB), 2006)
Given that savings behaviour and worker productivity have strong life-cycle components and given that demographic profiles vary across countries, population age structure should be linked to differences in levels of economic development. In this paper we measure the economic importance of age structure variation for the global economy. We find that even after adjusting for country-specific effects, demographic maturation has been associated with nearly half of the evolution of global per-capita GDP since 1960. We also find that age structure differences can account for just over half of the variation in worldwide per capita GDP (i.e. the lack of sigma convergence) observed since 1960. Taken as a whole, these results complement recent theoretical and empirical work on the importance of population size and economic development and reinforce empirical work linking mature demographic age structures with faster cross-country economic growth rates.
Keywords: J13; J22; J24; O11; O40; 330; age structure; cross-country growth; life cycle savings model; Nationaleinkommen; Sparen; Lebenszyklus; Welt; Altersstruktur